(untitled) (Web of Teachers: Inderscience Research, 2025)
This article highlights the effects of visual content on the formation of human memory. For example, the effects of image, visual and other visual information on the brain, how they are processed, and factors that contribute to long-term memory retention will be analyzed. Basic recommendations are also given on the conscious use of digital technologies and maintaining psychological stability. In addition, Dual- coding theory, such as the role of emotional impact, color, and movement are explained. The article reveals the good aspects of education, marketing and the use of visual materials in everyday life.